2022
DOI: 10.3389/fcell.2022.1038107
|View full text |Cite
|
Sign up to set email alerts
|

Squeezing the eggs to grow: The mechanobiology of mammalian folliculogenesis

Abstract: The formation of functional eggs (oocyte) in ovarian follicles is arguably one of the most important events in early mammalian development since the oocytes provide the bulk genetic and cytoplasmic materials for successful reproduction. While past studies have identified many genes that are critical to normal ovarian development and function, recent studies have highlighted the role of mechanical force in shaping folliculogenesis. In this review, we discuss the underlying mechanobiological principles and the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 231 publications
1
14
0
Order By: Relevance
“…Here we are particularly interested in how the macrophages modulate their functions in response to the changing ECM environment during ovarian aging, which is accompanied by extensive fibrosis. Some of these questions are highlighted in a recent review published by our lab ( 2 ).…”
Section: What Are the Main Research Lines That You Have Set Up To Stu...mentioning
confidence: 99%
“…Here we are particularly interested in how the macrophages modulate their functions in response to the changing ECM environment during ovarian aging, which is accompanied by extensive fibrosis. Some of these questions are highlighted in a recent review published by our lab ( 2 ).…”
Section: What Are the Main Research Lines That You Have Set Up To Stu...mentioning
confidence: 99%
“…In addition, recent studies have revealed that the ovarian stroma surrounding follicles also regulates the follicular microenvironment, both mechanically and biochemically. [1][2][3] Furthermore, recent research has revealed that the accumulation of senescent cells worsens the adverse local environment in various tissues and plays critical roles in pathological conditions and chronological aging. 4 Cellular senescence is characterized by cell-cycle arrest, a senescence-associated secretory phenotype (SASP), macromolecular damage, and dysmetabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The follicular microenvironment consists of the oocyte, the surrounding somatic cells (granulosa cells [GCs] and theca‐interstitial cells [TICs]), and the follicular fluid. In addition, recent studies have revealed that the ovarian stroma surrounding follicles also regulates the follicular microenvironment, both mechanically and biochemically 1–3 . Furthermore, recent research has revealed that the accumulation of senescent cells worsens the adverse local environment in various tissues and plays critical roles in pathological conditions and chronological aging 4 …”
Section: Introductionmentioning
confidence: 99%
“…[10,14,15] for reviews). More recently, experimental advances made it possible to study also the mechanical properties [7,16,17] and its influences [6,[18][19][20][21][22] on cell development. Measuring the forces inside the ECM is very difficult for a variety of reasons.…”
Section: Introductionmentioning
confidence: 99%